Procedure-Related Temporal Infarct After Retractorless Transsylvian Selective Amygdalohippocampectomy and Impact on 2-Year Epilepsy Outcome. Issue 4 (1st August 2019) - Liao, Chih-Hsiang; Chen, Shao-Ching; Yu, Hsiang-Yu; Lin, Chun-Fu; Chou, Chien-Chen; Lee, Cheng-Chia; Lin, Chung-Jung; Hsu, Sanford P C; Shih, Yang-Hsin
Abstract: BACKGROUND: Selective amygdalohippocampectomy (SAH) is designed to treat patients with mesial temporal lobe epilepsy (MTLE). OBJECTIVE: To determine the volume and impact of temporal lobe infarction after retractorless transsylvian SAH (en bloc resection of the hippocampus) that have not been reported. METHODS: A retrospective analysis of patients treated with retractorless transsylvian SAH. Infarctions were detected by magnetic resonance imaging (MRI) within the first week after the operation. Neuropsychological testing was performed preoperatively and 6 mo later. Seizure outcome was evaluated 2 yr after epilepsy surgery. RESULTS: Between 2010 and 2014, a total of 30 patients were included in this study. Analysis of postoperative MRI showed the following: (1) mean removal volume of the hippocampus-parahippocampus was 5.72 cm 3, and (2) mean volumes of temporal and insular infarctions were 1.71 and 0.25 cm 3, respectively. Twenty-five patients (83.3%) were free of disabling seizures (Engel class I) at 2 yr of outcome. Neuropsychological testing revealed improvement in Perceptual Organization Index ( P = .036) and verbal paired associates II ( P = .014) after the operation. Neither infarction volume nor removal volume was related to epilepsy outcome in linear regression model. CONCLUSION: Transsylvian SAH has comparable seizure outcomes but bears inherent risks of vasospasm/vascular injury. Immediate postoperative small infarction volume around resection cavity or along surgical corridor was noticed after retractorless transsylvian SAH, which did not cause neuropsychological deteriorations, in contrast to previous study with the use of self-sustaining rigid retraction system. Further study should be performed to compare procedure-related infarctions and their impacts on neuropsychological outcomes in different selective approaches.